Identification of amino acid domains of Borrelia burgdorferi P66 that are surface exposed and important for localization, oligomerization, and porin function of the protein - Curtis, Michael W.; Fierros, Christa H.; Hahn, Beth L.; Surdel, Matthew C.; Kessler, Julie; Anderson, Phillip N.; Vandewalle-Capo, Marine; Bonde, Mari; Zhu, Jieqing; Bergström, Sven; Coburn, Jenifer (Frontiers in Cellular and Infection Microbiology, 2022)
P66, a bifunctional integral outer membrane protein, is necessary for Borrelia burgdorferi to establish initial infection and to disseminate in mice. The integrin binding function of P66 facilitates extravasation and dissemination, but the role of its porin function during murine infection has not been investigated. A limitation to studying P66 porin function during mammalian infection has been the lack of structural information for P66. In this study, we experimentally characterized specific domains of P66 with regard to structure and function. First, we aligned the amino acid sequences of P66 from Lyme disease-causing Borrelia and relapsing fever-causing Borrelia to identify conserved and unique domains between these disease-causing clades. Then, we examined whether specific domains of P66 are exposed on the surface of the bacteria by introducing c-Myc epitope tags into each domain of interest. The c-Myc epitope tag inserted C-terminally to E33 (highly conserved domain), to T187 (integrin binding region domain and a non-conserved domain), and to E334 (non-conserved domain) were all detected on the surface of Borrelia burgdorferi. The c-Myc epitope tag inserted C-terminally to E33 and D303 in conserved domains disrupted P66 oligomerization and porin function. In a murine model of infection, the E33 and D303 mutants exhibited decreased infectivity and dissemination. Taken together, these results suggest the importance of these conserved domains, and potentially P66 porin function, in vivo.